2011
DOI: 10.1203/pdr.0b013e3181fff35f
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Metabolism in Cystic Fibrosis and Primary Ciliary Dyskinesia

Abstract: Previous studies have reported differences in muscle function and metabolism between patients with cystic fibrosis (CF) and healthy controls (HC), but it is currently unknown whether these abnormalities are specific to CF or also seen in other airway diseases. In this study, we used magnetic resonance spectroscopy (MRS) during exercise to assess muscle metabolism in CF patients. Twenty patients with CF and 20 age, gender, and habitual activity-matched HCs and a respiratory disease comparison group with primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
98
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 38 publications
13
98
3
1
Order By: Relevance
“…An a priori sample size of 16 participants per group was calculated for determination for half-time PCr recovery, with a minimum detectable difference of 9 and SD of 9; power was set at 0.8 and ␣ ϭ .05. For secondary outcomes, including changes in pH after exercise (resting pH Ϫ end-exercise pH) values from HC children collected with similar protocols and equipment, we calculated that 12 participants per group would be sufficient to detect an effect size difference of 0.2, with an SD of 0.15 in pH change, at a significance of ␣ ϭ .05 and power of 0.8 (26).…”
Section: Discussionmentioning
confidence: 99%
“…An a priori sample size of 16 participants per group was calculated for determination for half-time PCr recovery, with a minimum detectable difference of 9 and SD of 9; power was set at 0.8 and ␣ ϭ .05. For secondary outcomes, including changes in pH after exercise (resting pH Ϫ end-exercise pH) values from HC children collected with similar protocols and equipment, we calculated that 12 participants per group would be sufficient to detect an effect size difference of 0.2, with an SD of 0.15 in pH change, at a significance of ␣ ϭ .05 and power of 0.8 (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, muscle metabolism seems to be impaired, especially during high-intensity exercises [35]. Malnutrition and electrolyte disturbances [36], physical inactivity [13,25], systemic inflammation [37], oxidative stress [38], oral corticosteroid use [39] and CF-specific gene defects [35,40,41] are suggested to be involved in muscle dysfunction. Frequent exacerbations might further play a role in the long-term development of muscle dysfunction.…”
Section: Reasons For a Reduced Exercise Capacitymentioning
confidence: 99%
“…Thus, the hypothesis of specific physiological impairments in the CF skeletal muscles can be raised. Wells et al [9] found abnormalities in muscle metabolism in CF children as compared with age, sex and habitual physical activity (PA)-matched healthy controls, suggesting intrinsic dysfunction of skeletal muscle function. Lamhonwah et al [10] recently demonstrated that CF transmembrane conductance regulator (CFTR) is expressed at the sarcoplasmic reticulum of human skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%